Incidence, risk factors, and outcomes of central venous catheter‐related thromboembolism in breast cancer patients: the CAVECCAS study. (4th October 2017) - Debourdeau, Philippe; Espié, Marc; Chevret, Sylvie; Gligorov, Joseph; Elias, Antoine; Dupré, Pierre François; Desseaux, Kristell; Kalidi, Issa; Villiers, Stephane; Giachetti, Sylvie; Frere, Corinne; Farge, Dominique
Abstract: Previous epidemiologic studies investigating central venous catheter (CVC)‐related venous thromboembolism (CRT) were conducted in heterogenous cancer populations and data in breast cancer (BC) remain limited. To investigate the Doppler ultrasound (DUS)‐CRT incidence, risk factors and outcomes in BC, we designed a prospective, multicenter cohort of nonmetastatic invasive BC patients undergoing insertion of a CVC for chemotherapy. All patients underwent double‐blind DUS before, 7, 30, and 90 days after CVC insertion and a 6 months clinical follow‐up. Symptomatic DUS‐CRT were treated by anticoagulants. D‐Dimers, thrombin generation, and platelet‐derived microparticles were measured before and 2 days after CVC placement. In DUS‐CRT patients, a nested case–control study analyzed the role of thrombophilia. Among 524 patients, the DUS‐CRT (14 symptomatic, 46 asymptomatic) cumulative probability was 9.6% at 3 months and 11.5% at 6 months (overall incidence rate: 2.18/100 patient‐months). Ten/14 symptomatic DUS‐CRT were detected on double‐blind DUS before the clinical symptoms, and 3/14 had a simultaneous pulmonary embolism. No clinical thrombotic event subsequently occurred in untreated asymptomatic DUS‐CRT. Age >50 years (OR, 1.80; 95% CI, 1.01–3.22), BMI >30 kg/m² (OR, 2.64; 95% CI, 1.46–4.76) and comorbidities (OR, 2.05; 95% CI, 1.18–3.56) were associated with DUS‐CRT. No biomarkers was found to predict DUS‐CRT. In multivariate analysis, BMI >30 kg/m² (OR, 2.66; 95%CI, 1.46–4.84) and lobular carcinoma histology (OR, 2.56; 95%CI, 1.32–4.96) remained the only significant DUS‐CRT risk factors. Thrombophilia did not account for DUS‐CRT. Only clinical parameters identified high risk DUS‐CRT patients who may be considered for thromboprophylaxis. Abstract : Data regarding central venous catheter‐related thrombosis (CRT) in breast cancer (BC) patients are limited, although CVC placement for chemotherapy is common in this population and BC is the first cause of cancer in women worldwide. We conducted a large prospective multicentre study (9 cancer hospitals, 524 patients). The 6‐months cumulative probability of symptomatic and asymptomatic CRT was 11.5%. BMI >30 kg/m² and lobular carcinoma histology were the main risk factors for CRT.